2021
DOI: 10.3390/foods10020221
|View full text |Cite
|
Sign up to set email alerts
|

γ-PGA-Rich Chungkookjang, Short-Term Fermented Soybeans: Prevents Memory Impairment by Modulating Brain Insulin Sensitivity, Neuro-Inflammation, and the Gut–Microbiome–Brain Axis

Abstract: Fermented soybean paste is an indigenous food for use in cooking in East and Southeast Asia. Korea developed and used its traditional fermented foods two thousand years ago. Chungkookjang has unique characteristics such as short-term fermentation (24–72 h) without salt, and fermentation mostly with Bacilli. Traditionally fermented chungkookjang (TFC) is whole cooked soybeans that are fermented predominantly by Bacillus species. However, Bacillus species are different in the environment according to the regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 77 publications
2
31
0
Order By: Relevance
“…Recent studies demonstrated that the consumption of cheonggukjang fermented by Bacillus subtilis or Bacillus amyloliquefaciens increased the abundance of Bifidobacteriales and Lactobacillales in the gut. However, the population of Enterobacteriales, which are considered harmful bacteria, were lowered by a cheonggukjang-containing diet [126,127].…”
Section: Fermented Soy Products and Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies demonstrated that the consumption of cheonggukjang fermented by Bacillus subtilis or Bacillus amyloliquefaciens increased the abundance of Bifidobacteriales and Lactobacillales in the gut. However, the population of Enterobacteriales, which are considered harmful bacteria, were lowered by a cheonggukjang-containing diet [126,127].…”
Section: Fermented Soy Products and Gut Microbiotamentioning
confidence: 99%
“…The intake of cheonggukjang fermented with Bacillus species prevents and alleviates the memory impairment observed in patients with AD and cerebral ischemic condition. In particular, cheonggukjang, which contains a high poly-L-γ-glutamic acid (γ-PGA), exhibited better efficacy for improving glucose metabolism and neuronal cell survival than did a low level of γ-PGA [126], although the neuroprotective effect and related mechanism(s) of γ-PGA remain unclear.…”
Section: Gut Microbiota and Admentioning
confidence: 99%
“…Besides, recent evidence suggested that short-term fermented soybean intake can be protective against memory impairment and Alzheimer’s disease in humans by suppressing insulin resistance in the brain, preventing neuroinflammation, and modulating the gut–microbiome–brain axis [ 200 ].…”
Section: Fermented Soy Productsmentioning
confidence: 99%
“…Cheonggukjang (CGJ) is a traditional Korean dish produced by fermenting boiled soybeans rice straw, which naturally contains Bacillus subtilis . Fresh CGJ is prepared by spreading rice straw on boiled soybeans and keeping them warm at 40–50 °C for 2–3 days ( Figure 1 A) [ 1 , 2 , 3 , 4 , 5 ]. During the fermentation process of CGJ, soy protein is decomposed into amino acids by potent proteolytic enzymes produced by B. subtilis ( Figure 1 B), thus improving digestibility and increasing the vitamin B 2 and calcium contents of the final product [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, raw and powdered forms of CGJ are being developed. Unlike natto, which is a traditional Japanese dish consisting of fermented soybeans, and other soybean-fermented pastes in Asia that are eaten raw, CGJ does not contain salt, but can include ingredients such as crushed green onions, garlic, and red pepper powder for flavor, and salt can be added to the boiled soybeans to extend the product’s shelf life [ 3 , 4 , 5 ]. This provides an advantage over kimchi and other soybean paste products that contain high salt concentrations, a factor that is associated with gastric cancer and high blood pressure [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%